Disability, the Politics of Maiming, and Higher Education in Palestine - Yasmin Snounu; Phil Smith; Joe Bishop (Disability Studies Quarterly, 2019)
Different pieces of a puzzle are put together to unpack the implications of biopolitical forms in relation to disability in Palestine. Tracing the political connections between Israel and the United States of America (the U.S.), both countries give themselves the right to maim the Palestinians in different forms. Israel maims the indigenous Palestinians in more direct ways, while the U.S. is the guard and supporter of Israel in the process of maiming the Palestinians. Yet, successful, disabled Palestinians have emerged from under the rubble in different fields and in academia and higher education in particular. In this paper, Critical Disability Studies (CDS) and Critical Discourse Analysis (CDA) are used as theoretical frameworks to examine disability in Palestinian higher education in light of political implications. The paper also reveals a dearth of research on disability in Palestinian higher education
Keywords: Israeli Apartheid; Disability; Palestinian Higher Education; Critical Disability Studies; Critical Discourse Analysis